USAGE OF EXERCISES IN THE PROCESS OF FORMATION OF FUTURE SPECIALISTS’ PROFESSIONAL COMPETENCE BY MEANS OF INTERNET TECHNOLOGIES - Serhiy S. Danylyuk (Інформаційні технології і засоби навчання, 2014)
The system of exercises which require usage of Internet technologies, taking into account such criteria as “specificity of perception of information on the Internet” and “predominant role of the formed competence” in the formation of future specialists’ professional competence is offered in the paper. Thus, in particular, according to the criterion of “the perception of information on the Internet” exercises are singled out, which are aimed at: the perception of the electronic text (i.e., speed reading); structured information perception; anticipation of content of information. In their turn, according to the criterion of “the dominant role of the formed competence” exercises are singled out which are aimed at establishing: speech competence (critical reading and listening); compensatory competence (exercises aimed at developing the ability and willingness to overcome the shortage of foreign knowledge, such as reading and listening); educational-and-cognitive competence (ability to use reference books, various dictionaries, the Internet resources).